AMBIENT AIR POLLUTION IN INDUSTRIAL WORKPLACES: RISK ASSESSMENT OF POLLUTANT EXPOSURE AND RESPIRATORY HEALTH OUTCOMES - Veronika, Erna; Simatupang, Meithyra Melviana; Irfandi, Ahmad; Azteria, Veza; Nitami, Mayumi (Universitas Medan Area, 2025)
Workers represent a population at risk of exposure to air pollutants in the workplace, rendering them vulnerable to various health impacts, particularly respiratory disorders. This condition is attributed to prolonged inhalation exposure over time. This study aims to assess the magnitude of health risks associated with occupational exposure to air pollutants and to identify respiratory complaints among workers. This study employed a descriptive quantitative design, utilizing risk assessment methods to estimate the exposure risk levels of carbon monoxide (CO), nitrogen dioxide (NO₂), ozone (O₃), and total suspended particulate (TSP) in the workplace. The study population comprised production workers, selected via simple random sampling. The risk estimation indicated that the concentrations of CO, O₃, and TSP, were within acceptable safety limits. However, exposure to NO₂ exceeded safe thresholds, presenting non carcinogenic risks to workers with an average body weight of 66,48 kg, a daily exposure duration of 7,583 hours, and an annual exposure frequency of 236,99 days over a 12,85-year period. A significant proportion of workers reported respiratory symptoms and had previously been diagnosed with acute respiratory infections (ARI). Consequently, consistent use of personal protective equipment (PPE), particularly masks, is highly recommended to mitigate exposure to airborne pollutants.